A soft X-ray activated lanthanide scintillator for controllable NO release and gas-sensitized cancer therapy. Issue 2 (18th September 2019) - Jiang, Mingyang; Xue, Zhenluan; Li, Youbin; Liu, Hongrong; Zeng, Songjun; Hao, Jianhua
Abstract : A soft X-ray activated scintillator-based light transducer for controllable NO release was developed for gas-sensitized in vivo tumor therapy. Abstract : Multifunctional light stimuli-responsive NO-based gaseous theranostic systems are highly desirable due to them directly killing cancer cells at high concentration (>1 μM) with minimized adverse effects. However, on-demand NO-releasing nano-platforms for deep-tissue gas-based cancer therapy have not yet been explored. Herein, we develop a new type of soft X-ray-activated NaYF4 :Gd/Tb scintillator as a light transducer for depth-independent NO release and on-demand gas-sensitized cancer therapy. Benefiting from the excellent radioluminescent property of NaYF4 :Gd/Tb, deep-tissue (up to 3 cm) NO release can be achieved by ultralow dosage soft X-ray (45 kVp, 0.18–0.85 mGy) irradiation. More importantly, the designed scintillator-based NO gasotransmitter presents significant inhibition of tumor growth under ultralow dosage soft X-ray irradiation. Therefore, such a soft X-ray activated NO-releasing nanoplatform provides a promising depth-independent gaseous therapy mode for defeating deep-seated cancer in the future.